2022
DOI: 10.3847/1538-4357/ac6ef8
|View full text |Cite
|
Sign up to set email alerts
|

The 26Al Production of the ν e -process in the Explosion of Massive Stars

Abstract: The core collapses of massive stars at the ends of their lives will produce powerful streams of neutrinos, which provide an important contribution to the 26Al yield during the explosion stage. In this work, the contribution of the process 26 Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…If the shock wave velocity is slower and arrives later, more of the 74 As will be produced with a more powerful neutrino flux. There will be more 74 As produced if the shock velocity is as low as possible; however, too low a shock velocity may cause the explosion to fail (Li & Li 2022). By analyzing the abundance of 74 Se contributed by the ν-process, it is found that when the average shock wave velocity υ sh = 5000 km s −1 and the initial radius r 0 = 8600 km, the maximum abundance ratio of 74 Se and 74 Ge was (10.9 ± 2.2) × 10 −4 from experimental B(GT) values with neutrino temperatures of 2.8 MeV.…”
Section: Gementioning
confidence: 99%
“…If the shock wave velocity is slower and arrives later, more of the 74 As will be produced with a more powerful neutrino flux. There will be more 74 As produced if the shock velocity is as low as possible; however, too low a shock velocity may cause the explosion to fail (Li & Li 2022). By analyzing the abundance of 74 Se contributed by the ν-process, it is found that when the average shock wave velocity υ sh = 5000 km s −1 and the initial radius r 0 = 8600 km, the maximum abundance ratio of 74 Se and 74 Ge was (10.9 ± 2.2) × 10 −4 from experimental B(GT) values with neutrino temperatures of 2.8 MeV.…”
Section: Gementioning
confidence: 99%
“…The neutrino interactions include charged-(CC) and neutral-current (NC) reactions. Although the neutrino interactions with nuclei are usually negligible, the ν process can contribute entirely or to a significant portion of the production of a handful of rare isotopes including 7 Li, 11 B, 15 N, 19 F, 92 Nb, 98 Tc, 138 La and 180 Ta, as well as two radioisotopes 22 Na and 26 Al (Woosley et al 1990;Heger et al 2005;Byelikov et al 2007;Yoshida et al 2004Yoshida et al , 2005Yoshida et al , 2006aByelikov et al 2007;Yoshida et al 2008;Hayakawa et al 2008Hayakawa et al , 2010Nakamura et al 2010;Austin et al 2011;Cheoun et al 2012;Suzuki and Kajino 2013;Rauscher et al 2013;Hayakawa et al 2013;Lahkar et al 2017;Sieverding et al 2018;Hayakawa et al 2018;Olive and Vangioni 2019;Malatji et al 2019;Kusakabe et al 2019;Li and Li 2022;.…”
Section: ν-Process Nucleosynthesis and Neutrinosmentioning
confidence: 99%